Numerical investigations on the turbulent forced convection of nanofluids flow in a triangular-corrugated channel - Ahmed M.A.; Yusoff M.Z.; Ng K.C.; Shuaib N.H. (Elsevier Ltd, 2023)
Aluminum; Channel flow; Finite volume method; Forced convection; Heat transfer; Heat transfer coefficients; Nanoparticles; Reynolds number; Turbulent flow; Volume fraction; Zinc oxide; Corrugated channel; Governing equations; Heat Transfer enhancement; Low Reynolds number; Nanofluids; Numerical investigations; Thermal-hydraulic performance; Turbulent forced convection; Nanofluidics